Kajian Teknis Penerangan Jalan Umum di Jalan Akses Bandara Juanda - Sunarto, Rizqi Kusumawardana; Andriawan, Aris Heri; Wardah, Izzah Aula (Lembaga Yasin AlSys, 2023)
Juanda Airport Access Road, Sidoarjo Regency, East Java has a length of 3.15km with a width of 6m and there are 73 lighting points with a pole height of 12m and a distance between poles of 44m with a total of 8 single-arm poles and 65 double-arm poles. In addition, the street lighting lamps installed are 72 150 watt LED lamps and 66 250 watt SON-T type lamps. The measurement results are 26.37 lux for a 150 watt LED type lamp and 10.27 lux for a 250 watt SON-T lamp. However, from the many lights that have been installed, the lighting on the access road to Juanda Airport is still not optimal and many blackspots are found in certain areas. Therefore, it is necessary to do a re-analysis so that the road lighting for the Juanda Airport access road can meet the standards. The results of the analysis concluded that by carrying out a simulation on the dialux application according to the conditions in the field, 73 points of lighting poles were needed, the handlebar angle of the ornament was 14.06o with a total of 138 196 watt LED lights with an intensity of 15 lux which was in accordance with the standards of the Indonesian National Standards Agency 7391 : 2008 regarding the specifications for street lighting in urban areas and the Ministry of Energy and Mineral Resources 2014 for collector road classes for national road status, namely 15 - 20lux.